2023
DOI: 10.2147/idr.s411125
|View full text |Cite
|
Sign up to set email alerts
|

The Resistance and Virulence Characteristics of Salmonella Enteritidis Strain Isolated from Patients with Food Poisoning Based on the Whole-Genome Sequencing and Quantitative Proteomic Analysis

Benjin Xu,
Zhuru Hou,
Ling Liu
et al.

Abstract: Objective This paper explores the drug resistance, genome and proteome expression characteristics of Salmonella from a food poisoning event. Methods A multidrug-resistant Salmonella Enteritidis strain, labeled as 27A, was isolated and identified from a food poisoning patient. Antimicrobial susceptibility testing determined the resistance of 27A strain to 14 antibiotics. Then, WGS analysis and comparative genomics ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
2
1
0
Order By: Relevance
“…In this study, MLST analysis showed that all 43 strains of S . enteritidis were ST11 type, and included seven housekeeping genes, consistent with a previous report [ 41 , 42 ]. The results indicated close correlations between sporadic S .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study, MLST analysis showed that all 43 strains of S . enteritidis were ST11 type, and included seven housekeeping genes, consistent with a previous report [ 41 , 42 ]. The results indicated close correlations between sporadic S .…”
Section: Discussionsupporting
confidence: 88%
“…MLST is a classical bacterial molecular typing technique widely used to identify relationships among bacterial clones [40]. In this study, MLST analysis showed that all 43 strains of S. enteritidis were ST11 type, and included seven housekeeping genes, consistent with a previous report [41,42]. The results indicated close correlations between sporadic S. enteritidis in Huzhou.…”
Section: Plos Onesupporting
confidence: 90%
“…These findings were consistent with the results presented in the present study. In this food poisoning incident, an ST11 S. enterica 27A strain had been previously isolated ( Xu et al 2023 ). It shares the same genotype, serotype, and plasmid replicon as the 21A strain in this study, but the clinical symptoms caused by the two strains have slight differences.…”
Section: Discussionmentioning
confidence: 99%